Rotation models for the Galilean satellites. (15th September 2022) - Bills, Bruce G.; Scott, Bryan R.
Abstract: The primary objective of the present study is to develop and present improved models of the rotational motions of the Galilean satellites Io, Europa, Ganymede, and Callisto. The models include both precessions and nutations of the spin poles, and forced librational oscillations of the rotation rates. Gravitational torques acting on the triaxial figures of these bodies cause their spin poles to precess about their instantaneous orbit poles, whose orientations are quite well known. It is generally expected that the obliquity, or angular separation between spin and orbit poles, for these bodies is small. As a result, there are not yet any good measurements of those angles and thus, the current IAU models for the spin pole motions of these bodies assume zero obliquity. Those models also ignore long period forced librations, driven by deviations of the orbital mean longitudes from linear trends in time. However, near-term future missions to Europa and Ganymede will soon change that situation for the better. We employ a simple model in which the spin pole precessional motion is assumed to be fully damped, and well-known variations in orbital mean longitude drive the librations. Our intent is to both present current estimates of the relevant parameters, and to describe the process used to obtain them, in enough detail to aid in developing better models when the relevant data become available.